Establishment of the mechanism of purification and levigation of green chemistry-assisted biocomposites of red ochre (Gairika): synthesis, characterization, and antibacterial, prebiotic, antioxidant, and antacid activities of the traditional Ayurvedic medicine Laghu Sutashekhara Rasa - Charde, Vaibhav; Kumar, Vijay; Dane, Ganesh; Gandhi, Yashika; Soni, Hemant; Jagtap, Chandrashekar; Mishra, Sujeet K.; Shakya, Santosh K.; Singh, Arjun; Singh, Ravindra; Sharma, Bhagwan S.; Khanduri, Shruti; et al. (Frontiers in Chemistry, 2023)
Gairika (red ochre) has a long history of influencing human civilization. Gairika is a rich source of nutrients used for reproductive and brain health. Gairika is mentioned as an antacid drug in Indian Ayurvedic medicine under Laghu Sutashekhara Rasa (LSR). However, a detailed study on LSR has not been reported to date. In the present study, LSR was prepared, and a pharmaceutical SOP (standardization procedure) was reported to obtain batch-to-batch reproducibility. LSR was characterized using FTIR, XRD, SEM-EDX, and TGA analyses. LSR was tested in vitro for its antacid activity. Advanced instrumentation revealed that LSR formation produced symmetrical particles (5–8 µm) with kaolin, kaolinite, quartz, goethite, and hematite, along with the phytoconstituents of Goghrita (clarified cow’s butter), Shunthi, and Nagawalli, as confirmed by GC-MS/MS analysis. The FTIR study revealed the formation of a chelating complex of goethite and hematite along with their phytoconstituents. XRD analysis confirmed the presence of kaolin, kaolinite, quartz, goethite, and hematite. Using in vitro antacid experiments, LSR and Shunthi demonstrated significant antacid activity as compared to antacid drugs and standards in the market, such as CaCO3. The DPPH assay revealed IC50 values of 12.16 ± 1.23 mg/mL, which is 0.0029 of Trolox-equivalent antioxidant activity. The inhibition (18 ± 4 mm) against pathogens (S. aureus, E. coli, P. aeruginosa, and B. subtilis) and the prominent growth of gut microbiota-supported strains (S. boulardii, L. paracasei, and L. plantarum) observed on LSR formulation were indicative of LSR application as a prebiotic. Here, the mechanism of purification and levigation mentioned in the classical literature of LSR was established. Overall, purification of Gairika with cow ghee and levigation with Nagawalli may enhance the solubility, bioavailability, and shelf-life of LSR through hydration and co-crystallization mechanisms. This is the first comprehensive report on the pharmaceutical validation of LSR and its characterization. The results of the present study could contribute to the development and reliable reproduction of LSR and the utility of environmental red ochre as a medicine in combination with Shunthi (Zingiber officinale Roxb.), as prescribed under Indian Ayurvedic medicine.